Exciton coherence length fluctuations in chromophore aggregates probed by multidimensional optical spectroscopy - Šanda, František (American Institute of Physics, 2010)
The coherent third order optical response of molecular aggregates with fluctuating frequencies, couplings, and transition dipole moments is studied. We derived stochastic nonlinear exciton equations (SNEEs) by combining the quasiparticle picture of excitons with the path integral over stochastic bath paths described by the stochastic Liouville equations. Coherent two-dimensional (2D) spectra are calculated for a tetramer model system whose transition dipole orientations undergo two-state stochastic jumps on an arbitrary timescale. Correspondence between domains of ordered dipoles, which determine the exciton coherence length and the absorption peaks, is established. Signatures of domain coherence length fluctuations are observed in the cross peak dynamics of the 2D spectra in specific pulse polarization configurations.